True blood. The complete sixth season [videorecording (DVD)] - Ball, Alan, 1957-
Season six introduces several jarring storylines. As "Billith" comes to terms with his newfound powers after emerging from a pool of blood at the end of season five, Louisiana governor Truman Burrell declares open season on vampires, replete with novel anti-vamp weapons and high-tech internment camp. Sookie and Jason steel themselves for an encounter with the killer of their parents; the mysterious and ancient Warlow.